2009
DOI: 10.3892/ijo_00000447
|View full text |Cite
|
Sign up to set email alerts
|

Cigarette smoke-induced DNA damage and repair detected by the comet assay in HPV-transformed cervical cells

Abstract: Abstract. Human papillomavirus (HPV) is the causative factor in the development and progression of cervical cancers in >97% of the cases, although insufficient. Epidemiological studies suggest an elevated risk of cervical cancer for cigarette smokers; therefore, we examined cigarette smoke-induced DNA damage and repair in HPV16-transformed human ectocervical cells (ECT1/E6 E7). Cells were treated with cigarette smoke condensate (CSC) for 72 h to assess the formation of single-and double-strand DNA breaks, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 60 publications
1
3
0
Order By: Relevance
“…In the present and our previous studies [21], we consistently observed that the level of total POB-DNA adducts in HPV-positive cells was significantly higher than that in HPV-negative cells, suggesting synergistic carcinogenesis of HPV and NNK. Moktar et al [45] reported that single-and double-strand DNA breaks induced by cigarette smoke condensate were dose-dependent and persistent in HPV-transformed human ectocervical cells, which gave support to our results. To prevent the synergistic DNA-damaging function of HPV and NNK, we tried to discover a natural product as a potential chemopreventive agent against the synergistic carcinogenesis of HPV and NNK.…”
Section: Discussionsupporting
confidence: 90%
“…In the present and our previous studies [21], we consistently observed that the level of total POB-DNA adducts in HPV-positive cells was significantly higher than that in HPV-negative cells, suggesting synergistic carcinogenesis of HPV and NNK. Moktar et al [45] reported that single-and double-strand DNA breaks induced by cigarette smoke condensate were dose-dependent and persistent in HPV-transformed human ectocervical cells, which gave support to our results. To prevent the synergistic DNA-damaging function of HPV and NNK, we tried to discover a natural product as a potential chemopreventive agent against the synergistic carcinogenesis of HPV and NNK.…”
Section: Discussionsupporting
confidence: 90%
“…It has been demonstrated that HPV16 and 18 infected cells are capable of generating high levels of BaP metabolites, thus increasing adduct formation, DNA damage and probably, favoring the possibility of HPV integration into the host [138]. In accordance with this finding, HPV-transformed cervical cancer cells were highly susceptible to DNA damage promoted by CSE, detected by comet assay [139]. Interestingly, Wei et al found increased DNA mutations and double strand breaks in CIN I cells harboring episomal HPV after TS exposure [101].…”
Section: Tobacco Smoke Promotes Dna Damage Leading To An Increased Hpmentioning
confidence: 58%
“…Moktar et al, 2009 reported that cigarette smoke condensate-mediated DNA strand breaks are highly persistent, and suggest that persistence of cigarette smoke-associated DNA damage in the presence of HPV infection may lead to increased mutations in cervical cells and ultimately higher cancer risk [ 29 ], however, in our study the status of smoking was not ascertained.…”
Section: Discussionmentioning
confidence: 83%